Optimization of the Purifying Process for Columbianetin-β-D-Glucopyranoside from Angelicae Pubescentis Radix and Evaluation of Its Analgesic Activity Using Hot Plate Test. (4th August 2021) - Zhang, Yaqian; Yang, Yuqiao; Shang, Ye; Liang, Chunxiao; He, Jun; Li, Jin; Chang, Yanxu
Abstract : The objective of this work was to provide an economic and practical method for the purification of columbianetin- β -D-glucopyranoside from Angelicae Pubescentis Radix extract. In the static adsorption and desorption, the effects of resin type (D101, HP-20, AB-8, GDX-201, and DA201), contact time (10–360 min), and temperature (298–318 K) were assessed on columbianetin- β -D-glucopyranoside adsorption efficiency in laboratory. GDX-201 resin showed the best adsorption and desorption properties for columbianetin- β -D-glucopyranoside. The kinetic data revealed that the equilibrium time for columbianetin- β -D-glucopyranoside adsorption was achieved within 150 min. Moreover, the adsorption kinetic curve was well in accordance with the pseudo-second-order equation ( R 2  > 0.99). The rate controlling step of the adsorption process was the intraparticle diffusion. The Langmuir isotherm models ( R 2  > 0.99) could describe the whole adsorption process, which was exothermic and spontaneous according to the result of thermodynamics tests. In the dynamic adsorption and desorption process, the optimum loading flow (4, 5, and 6 BV/h), ethanol concentration (0–60%), and elution volume (10–230 mL) were optimized. Under optimal conditions of 4 BV/h loading flow, 6.7 BV loading volume, 25% ethanol, and 14 BV elution volume, the content of columbianetin- β -D-glucopyranoside in the product was increased 29.61-fold from 0.45% to 13.32 ± 0.64% with yield of 88.03 ± 2.76% by an experiment of lab-scale enlargement. Then, columbianetin- β -D-glucopyranoside was further purified by PHPLC and its purity was more than 98%. Additionally, the analgesic activity of the columbianetin- β -D-glucopyranoside was assessed by hot plate test. The experimental results showed that columbianetin- β -D-glucopyranoside significantly increased the latency of pain response in mice. This study demonstrated columbianetin- β -D-glucopyranoside could be as a potentially natural analgesic component. It could be summed up that the established method was successfully applied to purifying columbianetin- β -D-glucopyranoside from Angelicae Pubescentis Radix extract.